Transnasal prelacrimal approach to the inferior intraconal space: a feasibility study. Issue 9 (1st July 2019) - Li, Lifeng; London, Nyall R.; Silva, Samuel; Prevedello, Daniel; Carrau, Ricardo L.
Abstract : Background: Endonasal access to the inferomedial and inferolateral intraconal space via the orbital floor has not been reported. The primary purpose of this study was to assess the feasibility of accessing the inferior intraconal space through the orbital floor via a transnasal prelacrimal approach. Secondarily, it aims to highlight anatomical relationships of neurovascular structures in this space, as a requirement to prevent complications. Methods: Six cadaveric heads (12 sides) were dissected using a transnasal prelacrimal approach. The orbital floor, medial to the infraorbital canal, was removed and the periorbita opened to expose the inferior rectus muscle. The inferomedial and inferolateral intraconal space was accessed alongside the medial and lateral border of inferior rectus muscle, respectively. Various anatomical relationships of adjacent neurovascular structures were recorded, and the distances among the recti muscles and optic nerve were also measured. Results: The infraorbital nerve is located at the inferolateral aspect of inferior rectus muscle. In the inferomedial intraconal space, we identified the inferomedial muscular trunk of the ophthalmic artery, optic nerve, and branches of the oculomotor nerve; whereas the inferolateral intraconal space contained the inferolateral muscular trunk of ophthalmic artery, branches of the oculomotor and nasociliary nerve, and abducens nerve. Distances from the medial, inferior, and lateral recti muscles to the optic nerve were (mean ± standard deviation) 4.70 ± 1.18 mm, 5.60 ± 0.93 mm, and 7.98 ± 1.99 mm, respectively. Distances from the inferior rectus muscle to the inferior borders of medial and lateral recti muscles were 4.45 ± 1.23 mm and 8.77 ± 1.80 mm. Conclusion: It is feasible to access the inferior intraconal space through the orbital floor via a transnasal prelacrimal approach. The access may be subdivided into inferomedial and inferolateral corridors according to the entry point at the medial or lateral border of the inferior rectus muscle. Neurovascular structures in the inferior intraconal space are visualized directly, which should enhance their preservation.